2014
DOI: 10.1038/ncomms4566
|View full text |Cite
|
Sign up to set email alerts
|

Nucleic acid sensing by T cells initiates Th2 cell differentiation

Abstract: While T-cell responses are directly modulated by Toll-like receptor (TLR) ligands, the mechanism and physiological function of nucleic acids (NAs)-mediated T cell costimulation remains unclear. Here we show that unlike in innate cells, T-cell costimulation is induced even by non-CpG DNA and by self-DNA, which is released from dead cells and complexes with antimicrobial peptides or histones. Such NA complexes are internalized by T cells and induce costimulatory responses independently of known NA sensors, inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 52 publications
0
34
0
1
Order By: Relevance
“…IL-10 regulates innate and adaptive Th1 and Th2 responses (Huang et al, 2018). Released self-dsDNA from dying cells can directly stimulate CD4 T cells to induce Th2 cell differentiation and activation (Imanishi et al, 2014), but the role of M.tb DNA in this response was not investigated. Our in vivo studies also show that the cGAS/STING pathway contributes to generating Th2 cells and inhibiting Th1 cell expansion.…”
Section: Discussionmentioning
confidence: 99%
“…IL-10 regulates innate and adaptive Th1 and Th2 responses (Huang et al, 2018). Released self-dsDNA from dying cells can directly stimulate CD4 T cells to induce Th2 cell differentiation and activation (Imanishi et al, 2014), but the role of M.tb DNA in this response was not investigated. Our in vivo studies also show that the cGAS/STING pathway contributes to generating Th2 cells and inhibiting Th1 cell expansion.…”
Section: Discussionmentioning
confidence: 99%
“…Mice deficient in DNase I or DNase II develop a lupus like disease (26, 27) and animals or humans lacking TREX1 (DNase III) acquire a number of inflammatory diseases (28, 29). Additionally, others have shown that naked, isolated, host DNA can, if co-injected with antigen, act as an adjuvant on its own (2, 30, 31). …”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a Sendai virus-derived 546-nucleotide ligand of RIG-I enhanced immunogenicity of influenza DNA vaccine [70]. TLRs, RIG-I-like receptor (RLRs), inflammasome and STING-dependent cytosolic DNA sensor ligands can all initiate Th2 cell differentiation [71]. Ligands of the cytosolic DNA sensor DAI have also been shown to be efficient molecular adjuvant for DNA cancer vaccines [72].…”
Section: Ligands Of Pattern Recognition Receptorsmentioning
confidence: 99%
“…eRNA41H, shown to enhance DNA vaccine action [69]. STING ligand can initiate Th2 cell differentiation in mouse model [71]. Ligands to dsDNA sensor, DA1, shown to be efficient adjuvants for cancer DNA vaccines [72].…”
Section: Removal Of Bacterial Elementmentioning
confidence: 99%